7p+7=6(p+5)

Simple and best practice solution for 7p+7=6(p+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7p+7=6(p+5) equation:


Simplifying
7p + 7 = 6(p + 5)

Reorder the terms:
7 + 7p = 6(p + 5)

Reorder the terms:
7 + 7p = 6(5 + p)
7 + 7p = (5 * 6 + p * 6)
7 + 7p = (30 + 6p)

Solving
7 + 7p = 30 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
7 + 7p + -6p = 30 + 6p + -6p

Combine like terms: 7p + -6p = 1p
7 + 1p = 30 + 6p + -6p

Combine like terms: 6p + -6p = 0
7 + 1p = 30 + 0
7 + 1p = 30

Add '-7' to each side of the equation.
7 + -7 + 1p = 30 + -7

Combine like terms: 7 + -7 = 0
0 + 1p = 30 + -7
1p = 30 + -7

Combine like terms: 30 + -7 = 23
1p = 23

Divide each side by '1'.
p = 23

Simplifying
p = 23

See similar equations:

| 15x+183=33 | | -4(m-8)=3m-3 | | 2(x+3)(x-5)=0 | | 3x+y=42 | | 1/6-11/12x+1=6 | | x^3+6x^2+3x=-18 | | 5x+3x+4x=189 | | 3-4/5w=-9 | | 2y+43=2 | | x^3-3x^2-x=-3 | | 2(-2)+4y=-16 | | (x+8)2=(x+7)2 | | -6-5=-8+x | | -7c+1=-27 | | 9x^4-42x^3+49x^2=0 | | 128x^2-24x+9=0 | | 5/t-5-2/t | | (x+1)=17 | | -6x=2x+16 | | 2-x+4-2x+3(x+2)=180 | | 7(3x-11y)+2x-5(x-6y)= | | -3x^2+2x+1=0 | | 144=(2/7)q | | x^2=12x-61 | | 2(w-2)+8=4-7w | | -x^2+28x-160=0 | | 5/2x | | 32x^3-98x=0 | | 1/3x-15+2/x-3 | | 1/4k-(k+1/4)=1/16(k+4) | | 9=1.5y | | 260=490-(5/7)q |

Equations solver categories